DETERMINANTS OF ISLAMIC SOCIAL REPORTING IN ISLAMIC BANKS ACROSS ASEAN COUNTRIES - Rindy Dwi Ladista; Aryan Danil Mirza BR; Retno Yuni Nur Susilowati (Worksheet : Jurnal Akuntansi, 2026)
This study investigates the influence of profitability, third-party funds, and the Sharia supervisory board on Islamic Social Reporting (ISR) among ASEAN countries over the period 2022–2024. This study employs a quantitative approach using secondary data from Islamic banks in ASEAN countries during the period 2022–2024. The samples were selected using a purposive sampling technique, resulting in 51 observations, and the data were analyzed using panel data analysis with the assistance of E-Views software. This study found that profitability has no significant effect on ISR, third-party funds have a positive effect on ISR, and the Sharia Supervisory Board has no significant effect on ISR. This study has several limitations, including a short observation period (2022–2024) and a limited set of variables focusing only on financial and governance factors. Additionally, the ISR measurement relies on content analysis of annual reports, which may involve subjectivity and overlook the quality of disclosures. Future research is recommended to extend the study period, include additional variables, and broaden the sample scope to obtain more comprehensive and representative insights into ISR practices across ASEAN. Furthermore, a qualitative approach to examining the role of the Sharia Supervisory Board (SSB) is suggested to better understand its influence on the quality and depth of social reporting.